The Study of Vowel Space and Formant Structure in Mazani Language - Mohamad Sharifpoor; Mehdi Dehghan; Shima Matloubi; Soraya Khafri (University of Social Welfare and Rehabilitation Sciences, 2020)
Objective: One of the parameters showing the correct phonetic and phonological development is the correct and clear articulation of vowels is achieved by changing the shape of vocal cords through altering the height and position of the tongue and the movement of the lips and jaw. The tongue's height and position are the basis of the production and difference of vowels. In other words, the raw sound produced by vocal cords, which has a base frequency, changes and intensifies according to the displacement of organs and vocal tract cavities which makes harmonies from the base sound called formats. These intensified harmonies depend on the shape, size, and material of the cavities, and can affect a person's speech clarity and, consequently, the listeners' perception. Due to such effects and the significant role of vowels space and formants on communicative aspects in each language, they are considered as one of the most important acoustic characteristics of any spoken language. Therefore, determining a scale as a tool to assess vowel errors and speech disorders is necessary. This study aimed to investigate vowel space and formant structure of Mazani language in adults. Materials & Methods: This descriptive-analytical study with a cross-sectional design was conducted on 60 adults (30 males and 30 females) with Mazani language aged 18-40 years who were selected randomly and based on the inclusion and exclusion criteria (no history of respiratory diseases, verbal and auditory disorders and having at least 5 years of experience in living in Babol county. After producing the vowels by participants, the first, second, and third formants (F1, F2, and F3) of all 6 vowels were obtained in PRAAT v.6.0 program, and analyzed finally using independent t-test in SPSS v. 18 software. Results: In men, the highest mean value for the base frequency was related to the vowels /i/ and /u/ (136 Hz), and for F1, F2, and F3, it was related to the vowels /æ/ (646 Hz), /i/ (2182 Hz), and /i/ (2888 Hz), respectively. On the other hand, their lowest mean values were related to the vowels /a/ (124 Hz), /i/ (283 Hz), /a/ (1150 Hz), and /e/ (2629 Hz), respectively. In women, the highest mean values of base frequency, F1, F2 and F3 were related to the vowels /u/ (222 Hz), /æ/ (828 Hz), /i/ (2346 Hz), and /i/ (3151 Hz), while the lowest mean values were related to the vowels /æ/ and /e/ (202 Hz), /i/ (364 Hz), /a/ (1167 Hz), and /o/ (2775 Hz), respectively. Conclusion: There was difference in formants and vowel space between men and women with Mazani language. The /a/ was the lowest pitch vowel and /i/ and /u/ were the highest pitch the vowels in men, while /æ/ and /e/ were the lowest pitch vowels and /u/ was the highest pitch vowel in women. Furthermore, the most open, closed, backward and forward vowels were /æ/, /i/, /i/ and /a/, respectively. The /e/ in men and /o/ in women were the most rounded vowels, while the /i/ in both genders was the most unrounded vowel. The results are somewhat different from the results of studies conducted on the production of vowels in standard Persian language. Since the speech clarity and fluency can be affected by the incorrect production of vowels, the results of this study can be used to evaluate and diagnose speech disorders in Mazani language for clinical and research purposes.